High expressions of CD10, FAP and GPR77 in CAFs are associated with chemoresistance and worse prognosis in gastric cancer - Tong, Yilin; Zhao, Zehua; Zhang, Jianjun; Wang, Wentao; Zhu, Yanmei (Frontiers in Oncology, 2022)
Introduction As neoadjuvant chemotherapy (NCT) has been successfully introduced in gastric cancer (GC), more biomarkers are needed to evaluate the efficacy. Cancer-associated fibroblasts (CAFs) is associated with chemoresistance and prognosis. Three biomarkers, CD10, fibroblast activation protein-α (FAP) and G-protein-coupled receptor 77 (GPR77), have been proved to express in CAFs. However, their predictive values for efficacy of NCT and prognosis in gastric cancer is unknown. Methods Totally, specimens of 171 locally advanced gastric cancer patients who underwent NCT and D2 radical gastrectomy and matched preoperative biopsy specimens were retrospectively analyzed. Tumor regression grade (TRG) is reevaluated according to Mandard TRG. Expressions of CD10, FAP and GPR77 in CAFs before NCT (pre-) and after NCT (post-) were evaluated by immunohistochemistry. Survival curves on overall survival (OS) were obtained by Kaplan-Meier method, and differences were analyzed by log-rank test. Associations between categorical variables were explored by chi-square test or Fisher’s exact method. Univariable and multivariate analyses were performed by logistic regression model and Cox proportional hazard regression model. Results High expressions of post-CD10, post-FAP, post-GPR77 and pre-CD10 were related to worse TRG (all p<0.05). In multivariable analysis, post- and pre-FAP were independent predictive factors to TRG (p<0.010). Post-CD10 (p=0.032) and post-FAP (p=0.013) were related to OS in univariable analysis, but none of biomarkers were independent prognostic factors in multivariable analysis. Conclusions Expressions of CD10, FAP and GPR77 in CAFs were related to chemoresistance and overall survival, and these biomarkers have predictive values for tumor regression and prognosis in locally advanced gastric cancer patients.